A long term follow-up study from India assessing the risk of diabetes mellitus in service population. Issue 2 (April 2018) - Kumar, K.V.S. Hari; Patnaik, S.K.
Abstract: Objective: The data about the incidence of diabetes is scarce from developing countries. We studied the incidence of type 1 (T1DM) and type 2 DM (T2DM) in a cohort of young military personnel followed for a long duration. Methods: The data for this descriptive epidemiologic study was derived from the electronic medical records (EMR) of the male service personnel enrolled between 1990 and 2015. All subjects were recruited before 18 years of age in good health and the onset of DM was derived from the EMR. We calculated the incidence rates as per person years using appropriate statistical methods. Results: Our study population includes 51, 217 participants (median age 33 years, range 17–54) with a mean follow up of 12.5 years, giving a cumulative follow up duration of 613, 925 person-years (py). A total of 251 patients developed T2DM and 15 patients developed T1DM during the study period. The incidence rate of T2DM was 0.41 per 1000 py and that of T1DM was 2.44 per 100, 000 py. Conclusion: Our cohort had low incidence rates of diabetes when compared with other studies from India and abroad. Active military service with good life style measures may offer protection from the DM.